Electrodeposition as an attractive method of NiCoP cathode catalyst for alkaline membrane water electrolysis production - Hnát, Jaromír; Ďurovič, Martin; Bystron, Tomas; Strečková, Magdaléna; Bouzek, Karel (Chemical engineering journal advances, 2025)
•Method of simple one-step catalyst synthesis and deposition developed.•Energy intensive steps and usage of dangerous components avoided.•Performance and stability tests in electrolysis cell provided.•Distribution of relaxation times method applied in EIS data analysis.•Question of appropriate A(M)WE EIS data treatment addressed. Phosphide-based materials are among the favourable catalysts due to their promising properties (catalytic activity, stability, and electrical conductivity) for hydrogen evolution reaction in both alkaline and acidic media. This study reports on preparation and subsequent characterisation of a non-platinum NiCoP catalyst for hydrogen evolution reaction (HER) using facile cathodic electrodeposition on a Ni support without toxic phosphorising agents. In the first step, catalyst synthesis optimisation was performed by monitoring the effect of (i) Ni:Co composition and (ii) phosphorus concentration in the deposition solution. Impact of these parameters on the composition as well as the HER electrocatalytic activity of the resulting catalyst was evaluated. Subsequently, the optimised NiCoP catalyst deposited on Ni foam was used as cathode for the HER in an alkaline membrane water electrolyser. It exhibited significant catalytic activity and promising stability. In summary, the cathodic electrodeposition proved to be a feasible method for producing an active and stable NiCoP catalyst for the HER in an alkaline media. This publication was supported by the following funding bodies: Ministry of Education, Youth and Sports of the Czech Republic, project "The Energy Conversion and Storage", funded as project No. CZ.02.01.01/00/22_008/0004617 by Programme Johannes Amos Commenius, call Excellent Research, Slovak Research and Development Agency under the contract no. APVV 20-0299. Technological Agency of the Czech Republic under the project No TK02030103 “Research and development of a reversible alkaline fuel cell”. [Display omitted]